Предмет: Геометрия, автор: vulka54

sin(180-a)-cos(90-a))*cos-tg(180-a)


Аноним: (sin(180-a)-cos(90-a))*cos(-tg(180-a)) ?
по формулам приведения
sin(180-a)=sin 180
Cos(90-a)= sin 90
-tg(180-a)= -(-tg 180)
значения
sin 180= 0
sin 90=1
tg 180=0
(0-1)*cos(0)=-1*1=-1

Ответы

Автор ответа: Аноним
2

Ответ: -1

Объяснение:

(sin(180-a)-cos(90-a))*cos(-tg(180-a)) ?

по формулам приведения

sin(180-a)=sin 180

Cos(90-a)= sin 90

-tg(180-a)= -(-tg 180)

значения

sin 180= 0

sin 90=1

tg 180=0

(0-1)*cos(0)=-1*1=-1

Похожие вопросы